Monitoring, Evaluation and Learning approaches in an adaptive management context - Tsui, Josephine (EPS PEAKS, ODI, 2016)

Doing things differently: Rethinking monitoring and evaluation to understand change - Saferworld (Saferworld, 2016)
Doing things differently: Rethinking monitoring and evaluation to understand change Learning paper Over the past four years, Saferworld has put in place a way of monitoring, evaluating and learning from our work focused on behaviour and relationship change. This paper outlines the process we have gone through to adapt, embed, and embrace an approach inspired by Outcome Mapping and Outcome Harvesting (OH). Key benefits of our monitoring, evaluation and learning approach are: It is simple, but promotes complex discussion and analysis. It allows conflict- and gender-sensitivity to be built into programmes; it promotes analysis of and adaptation to context. Bringing front-line staff and partners into wider conversations with others substantially increases cross-organisational learning.

SPACES MERL: Systems and Complexity White Paper - USAID (2016)
The Strategic Program for Analyzing Complexity and Evaluating Systems (SPACES MERL) project is an activity funded by USAID’s Global Development Lab and the Bureau for Policy, Planning and Learning (PPL). This three-year activity aims to bring a variety of tools and methodologies that decision-makers can use (alone or in combination) to provide comprehensive systems analysis. The activity is being implemented from 2015 to 2018 by a consortium of organizations expert in systems and complexity, including the Global Obesity Prevention Center (GOPC) at Johns Hopkins University (Prime), Global Knowledge Initiative (GKI), LINC and ResilientAfrica Network (RAN). This Systems and Complexity White Paper is a collaborative effort of the SPACES MERL team, designed to frame the international development landscape, with particular reference to USAID-funded activities, for application of systems and complexity approaches to design, monitoring and evaluation. Customized to the systems and complexity layperson with in-depth knowledge of international development practice, the objectives of this white paper are three-fold:  Provide an overview of systems and complexity practice, its current state of application and relevance to international development practice;  Establish a taxonomy of systems and complexity tools, highlighting the fit of those offered by SPACES MERL within the wider landscape; and  Review and provide information on application of SPACES MERL tools, their purpose and construction, required data, and their applicability to specific contexts.